2018
DOI: 10.32734/tm.v1i2.198
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Status Depresi Dengan Kualitas Hidup Lansia Di Kota Medan

Abstract: Gangguan mental biasa terjadi di usia tua tetapi keadaan ini sering tidak terdeteksi dan tidak diobati. Gangguan mental memicu terjadinya cacat fungsional, gangguan rehabilitasi, dapat membebani sistem kesehatan dan merusak kualitas hidup pasien tua serta keluarga mereka. Tujuan penelitian ini adalah untuk menganalisisi hubungan gangguan emosional (depresi) terhadap kualitas hidup lansia di Kota Medan.  Disain penelitian analitik dengan pendekataan cross sectional.  Populasi penelitian adalah seluruh lansia (&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
1
3
0
1
Order By: Relevance
“…From the results of the study that the female sex has a higher risk of depression than men. The results of this study are in line with research conducted by (Amelia et al, 2018) that the female gender has a higher risk of depression than the male gender. This is due to the impact of biological changes, namely hormonal and psychosocial women have a role that must be carried, which can be a stressor or trigger for depression ( (Ballo & Kaunang, 2012) in (Utami et al, 2018)).…”
Section: Depressionsupporting
confidence: 91%
See 1 more Smart Citation
“…From the results of the study that the female sex has a higher risk of depression than men. The results of this study are in line with research conducted by (Amelia et al, 2018) that the female gender has a higher risk of depression than the male gender. This is due to the impact of biological changes, namely hormonal and psychosocial women have a role that must be carried, which can be a stressor or trigger for depression ( (Ballo & Kaunang, 2012) in (Utami et al, 2018)).…”
Section: Depressionsupporting
confidence: 91%
“…The results of the research conducted (Amelia et al, 2018), obtained data that of all the elderly who did not experience depression, had a good quality of life, namely 8 people (9.52%), patients with moderate depression, 13 people ( 86.7%) had a moderate quality of life, and all patients with moderate to severe depression had a poor quality of life as much as 100%. The results of the Chi square test found that there was a significant relationship between depression status and the quality of life of the elderly (p<0.05).…”
Section: Bivariate Analysis Of the Relationship Between Depression Le...mentioning
confidence: 99%
“…The biggest impact that often occurs due to depression is a decreased quality of life (Stanley & Beare, 2007). This is following research by A.A. Ayu Rani Puspadewi and Etty Rekawati, where the results showed that there was a relationship between the level of depression and the quality of life of the elderly (Puspadewi & Rekawati, 2017) and were strengthened by the results of the research by Arlinda Sari Wahyunia, Julian Harahapa, and Rina Amelia which stated that there was a relationship between emotional disorders (depression) and the quality of life of the elderly in the city of Medan (Amelia et al, 2018). For this reason, efforts are needed to improve the quality of life of the elderly.…”
Section: Introductionmentioning
confidence: 65%
“…with the title, "Relationship of Family Support with Quality of Life for Elderly People with Hypertension In the Grujugan Hamlet, Bantul, Yogyakarta" and researchers(Amelia et al, 2018), with the title: "The Relationship between Depression Status and Quality of Life of the Elderly in Medan City. "…”
mentioning
confidence: 99%
“…Berdasarkan Hasil Analisis Uji Chisquare Didapatkan Hasil Dengan Nilai P=0,017 < 0,05 maka diperoleh kesimpulan adanya hubungan yang bermakna antara tingkat depresi dengan kualitas hidup lansia. Serta penelitian yang dilakukan oleh (Amelia et al,2018), diperoleh hasil penelitian yang menyatakan ada hubungan tingkat depresi dengan kualitas hidup (quality of life) pada lansia dengan p value = 0,0001.…”
Section: Analisis Statistikunclassified